Življenje in delo Jožefa Borovnjaka: Ed. Marko Jesenšek. Maribor: Faculty of Arts, Department of Slavic languages and literatures, 2008. Zora, 55. 323 p. - Benko, Anja (Slavia Centralis, 2020)
Life and work of Jožef Borovnjak The author presents a scientific monograph entitled Life and Work of Jožef Borovnjak (Življenje in delo Jožefa Borovnjaka), which was created on the basis of a symposium on the 150th anniversary of Borovnjak’s arrival as pastor in Cankova. The monograph was edited by Marko Jesenšek.